Diagnosis and management of selective fetal growth restriction in monochorionic twin pregnancies: A cross‐sectional international survey - Prasad, S; Khalil, A; Kirkham, JJ; Sharp, A; Woolfall, K; Mitchell, TK; Yaghi, O; Ricketts, T; Popa, M; Alfirevic, Z; Anumba, D; Ashcroft, R; et al. (Wiley, 2024)
Objective: To identify current practices in the management of selective fetal growth restriction (sFGR) in monochorionic diamniotic (MCDA) twin pregnancies. Design: Cross‐sectional survey. Setting: International. Population: Clinicians involved in the management of MCDA twin pregnancies with sFGR. Methods: A structured, self‐administered survey. Main Outcome Measures: Clinical practices and attitudes to diagnostic criteria and management strategies. Results: Overall, 62.8% (113/180) of clinicians completed the survey; of which, 66.4% (75/113) of the respondents reported that they would use an estimated fetal weight (EFW) of <10th centile for the smaller twin and an inter‐twin EFW discordance of >25% for the diagnosis of sFGR. For early‐onset type I sFGR, 79.8% (75/94) of respondents expressed that expectant management would be their routine practice. On the other hand, for early‐onset type II and type III sFGR, 19.3% (17/88) and 35.7% (30/84) of respondents would manage these pregnancies expectantly, whereas 71.6% (63/88) and 57.1% (48/84) would refer these pregnancies to a fetal intervention centre or would offer fetal intervention for type II and type III cases, respectively. Moreover, 39.0% (16/41) of the respondents would consider fetoscopic laser surgery (FLS) for early‐onset type I sFGR, whereas 41.5% (17/41) would offer either FLS or selective feticide, and 12.2% (5/41) would exclusively offer selective feticide. For early‐onset type II and type III sFGR cases, 25.9% (21/81) and 31.4% (22/70) would exclusively offer FLS, respectively, whereas 33.3% (27/81) and 32.9% (23/70) would exclusively offer selective feticide. Conclusions: There is significant variation in clinician practices and attitudes towards the management of early‐onset sFGR in MCDA twin pregnancies, especially for type II and type III cases, highlighting the need for high‐level evidence to guide management.